The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.22159/ajpcr.2018.v11i2.22674
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Efficacy of Gingival Retraction Using Chemical and Mechanical Methods: An in Vivo Study

Abstract: Objective: The purpose of this in vivo study was to compare and evaluate the clinical efficacy of two gingival retraction systems; Ultrapak and Traxodent, on the basis of the amount of gingival retraction achieved in vertical and horizontal direction and their hemorrhage control.Methods: A total of 60 subjects were selected requiring fixed prosthesis. The two gingival retraction systems were used on the prepared abutments randomly. The vertical gingival retraction was measured before and after retraction using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
0
1
Order By: Relevance
“…The current study results are contrary to other studies that documented that Ultrapak achieved significantly higher horizontal retraction than Traxodent 28,43 and another study reported that gingival displacement paste (Expasyl) showed better gingival sulcus widening than the retraction cord. 33 This might be due to different cord sizes, cordless material and evaluation methods.…”
Section: Discussioncontrasting
confidence: 99%
“…The current study results are contrary to other studies that documented that Ultrapak achieved significantly higher horizontal retraction than Traxodent 28,43 and another study reported that gingival displacement paste (Expasyl) showed better gingival sulcus widening than the retraction cord. 33 This might be due to different cord sizes, cordless material and evaluation methods.…”
Section: Discussioncontrasting
confidence: 99%
“…Kohli et al found that bleeding after retraction paste removal was statistically significantly lower compared to non-impregnated retraction cord (9). Same results were also reported in Jain AR et al study [14].…”
Section: Resultsmentioning
confidence: 55%
“…All included studies were in vivo and published in English. Different retraction methods were compared evaluating: bleeding after retraction [8][9][10]12,14], recessions [6,12,14], changes in clinical attachment level [7,13], tooth mobility [7,13], probing depth [7,13], plaque index [7,14], pain during retraction [6,13], inflammatory cytokine levels in gingival crevicular fluid (GCF) [13] and effect on the gingival sulcular epithelium [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation